2023
DOI: 10.1029/2022jc019195
|View full text |Cite
|
Sign up to set email alerts
|

Factors Controlling the Sea Surface Partial Pressure of Carbon Dioxide in Upwelling Regions: A Case Study of the Southern East China Sea Before and After Typhoon Maria

Abstract: Spatiotemporal variations in the partial pressure of surface carbon dioxide (pCO 2 ) in coastal upwelling regions are dynamic because of complex physical and biogeochemical responses (Borges & Frankignoulle, 2002;Hales et al., 2005). Upwelling systems in the tropical regions tend to act as carbon dioxide (CO 2 ) sources to the atmosphere because upwelling rapidly brings high amounts of CO 2 from cold and deep water into warm surface water (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 101 publications
0
1
0
Order By: Relevance
“…As a result of the TC "Wind Pump" effects, subsurface waters, which were colder and richer in CO 2 , were uplifted and mixed with the surface water. This dynamic process could lead to a decrease [20][21][22]37,38] or increase [16,17] in pCO 2-sw , depending on the dominant influence of cooling or carbon enrichment on carbonate chemistry [39].…”
Section: Wind Pump Effects Of Typhoon On Pco 2-swmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result of the TC "Wind Pump" effects, subsurface waters, which were colder and richer in CO 2 , were uplifted and mixed with the surface water. This dynamic process could lead to a decrease [20][21][22]37,38] or increase [16,17] in pCO 2-sw , depending on the dominant influence of cooling or carbon enrichment on carbonate chemistry [39].…”
Section: Wind Pump Effects Of Typhoon On Pco 2-swmentioning
confidence: 99%
“…Variations in these physical and biochemical processes may affect the concentration of pCO 2-sw . The degree of influence is determined by the typhoon's intensity, moving path, moving speed, precipitation, and the combined effects of the marine environment and other factors [14][15][16][17][20][21][22][23][24]. Nemoto et al (2009) discovered that three typhoons were responsible for approximately 60% of the CO 2 emissions during the summer season in the western subtropical North Pacific.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ye et al (2017) demonstrated that when Typhoon Wutip passed through the anticyclonic and cyclonic regions, the cyclonic region became a stronger carbon source, while the anticyclonic region changed from a carbon source to a carbon sink, which was primarily due to changes in vorticity, sea surface salinity (SSS), temperature, and pCO 2sea . Research by Kao et al (2023) indicated that when a typhoon occurs in the southern East China Sea, the factors affecting pCO 2sea in the upwelling area are the temperature effect (38%-40%), net biological activity (−33% to −36%), and the mixing effect (−24%).…”
Section: Introductionmentioning
confidence: 99%